Pemanfaatan Sistem Informasi Akuntansi (OSS, JELITA, SIMBG, MPP) dan Perizinan Usaha DPMPTSP Jember - Siti Wardatul Hasanah; Fadillahtul Hasanah; Asyiatur Rhodiyah; Mutmainnah Mutmainnah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The development of technology in each country affects its government sector, especially in the field of public services, one of which is e-government. E-government as a practice of social innovation in public administration, can be done easily but sometimes still experiences difficulties or even failures. Trying to help improve the efficiency and effectiveness of licensing services by operating the OSS, JELITA, SIMBG, and MPP systems. In addition, providing licensing services and public service malls and analyzing comprehensive investment data from each period with PMA and PMDN categories to identify growth trends, sectors that have experienced significant increases, and key driving factors such as government policies, economic conditions and investment attractiveness. The methods used in this service are system operation and analysis. This work experience practice provides valuable experience for practitioners in understanding the mechanisms of government administration, regional investment management, and business licensing procedures. In addition to gaining practical experience, this activity also improves analytical skills, communication, and professionalism in the world of work. This agency has the utilization of information systems that support the development of community activities Implementation of OSS, Jelita, SIMBG, services and MPP at DPMPTSP Jember which are useful for providing positive impacts and providing effectiveness in business licensing and community services with this success need to be maintained and through increasing digital literacy, system maintenance, data integration, and ongoing socialization.